2013
DOI: 10.1016/j.meegid.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Canine coronavirus, Greece. Molecular analysis and genetic diversity characterization

Abstract: Canine coronavirus (CCoV) is an etiologic agent of diarrhea in dogs and is known to have spread worldwide. Mild disease or asymptomatic carriage are probably in many cases common outcomes of infection. To date, two different genotypes of CCoV are known, CCoV type I (CCoV-I) and CCoV type II (CCoV-II). CCoV type II is divided in two subtypes, CCoV-IIa (classical strains) and CCoV-IIb, with CCoV-IIb emerging as a result of a putative recombination between CCoV-IIa and transmissible gastroenteritis virus (TGEV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 27 publications
3
41
2
2
Order By: Relevance
“…In the past decade, several researchers have studied the importance of CCoV as an agent of diarrhea in puppies Le Poder, 2011;Ntafis et al, 2013;Pratelli, 2011;Stavisky et al, 2012). In Brazil, despite the availability of safe and effective vaccines, CPV is considered the most common viral agent associated with enteritis in puppies (Castro et al, 2010b(Castro et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, several researchers have studied the importance of CCoV as an agent of diarrhea in puppies Le Poder, 2011;Ntafis et al, 2013;Pratelli, 2011;Stavisky et al, 2012). In Brazil, despite the availability of safe and effective vaccines, CPV is considered the most common viral agent associated with enteritis in puppies (Castro et al, 2010b(Castro et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the CCoV-II genotype was divided into two subtypes, CCoV-IIa (classical strains) and IIb (TGEV-like strains) (Decaro et al, 2009(Decaro et al, , 2010. Infection may occur with a single strain, but the two CCoV genotypes are commonly detected simultaneously in the same dog (Decaro et al, 2005(Decaro et al, , 2009Erles and Brownlie, 2009;Ntafis et al, 2013;Pratelli et al, 2004a;Pratelli, 2011) Since the first reports in 1971 (Binn et al, 1974), CCoV infection has been associated with mild cases of diarrhea. Clinical signs can range from moderate to severe, depending on whether the infection occurs in combination with other pathogens such as canine parvovirus (CPV), canine distemper virus or canine adenovirus type I (Decaro et al, 2004(Decaro et al, , 2007aPratelli et al, 1999aPratelli et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCoV infection have been reported from different countries Turkey (Gur et al, 2008), Italy , Greece (Ntafis et al, 2012), Belgium (Zicola et al, 2012), and detection has been reported from different specimens such as intestinal system (Keenan et al, 1976), feces (Battersby and Harvey, 2006;Ntafis et al, 2013;Costa et al, 2014), and internal organs like liver, lung, mesenteric lymph node and thymus (Ntafis et al, 2013). CCoV viral RNA detection from blood sample was reported by Decaro et al (2010) from one experimentally infected by CB/05 on dog (Decaro and Buonavoglia, 2011) during viremia.…”
Section: Resultsmentioning
confidence: 99%
“…To date, two different genotypes of CCoV are known, CCoV type I (CCoV-I) and CCoV type II (CCoV-II). CCoV type II is divided in two subtypes, CCoV-IIa (classical strains) and CCoV-IIb, with CCoV-IIb emerging as a result of a putative recombination between CCoV-IIa and transmissible gastroenteritis virus (TGEV) (Ntafis et al, 2013). Different serologic (indirect ELISA, microneutralization) (Mochizuki et al, 1987;Tuchiya et al, 1991;Elia et al, 2003;Buonavoglia et al, 2006;Le Poder, 2011) and virologic (direct ELISA, cell culture, direct immunofluorescence) diagnostic methods are widely used to detect the genotypes of CCoV (Costa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%